BrStudentMH: A Reddit Dataset for Mental Health Analysis in the Brazilian University Context - Marques, Maicon C.; Silva, Camila O.; Dallagnol, Leonardo P.; Rocha, Tiago C. B.; Ponciano, Jean R. (Anais do Dataset Showcase Workshop (DSW), 2026)
The increasing use of social networks has made platforms like REDDIT spaces for discussing sensitive topics without fear of judgment. This paper presents BrStudentMH, a dataset comprising 943 mental health-related posts and 15,680 comments in Brazilian Portuguese, collected from Brazilian higher education-related subreddits. The data were obtained through the REDDIT API and processed in a pipeline consisting of collection, categorization using Large Language Models, and pseudonymization. Its application is expected across various fields, providing insights into the mental health of Brazilian university students and contributing to the development of support and treatment policies.